The Influence Of Promotion, Consumer Trust And Service Quality On Purchasing Decisions On Online Transportation In Bengkulu City - Defa, Kikim Gumala; Nasution, Suswati; Zoniarti, Zoniarti (Sekolah Tinggi Ilmu Ekonomi Bentara Persada, 2024)
The factors of promotion, consumer trust, and service quality in the Maxim online transportation application in Bengkulu City are expected to influence consumers' purchasing decisions. Maxim is designed to facilitate consumers' travel, enabling them to travel easily and efficiently anytime and anywhere. The purpose of this research is to examine the influence of promotion, consumer trust, and service quality on purchasing decisions for online transportation in Bengkulu City. The sample in this study consists of 100 Maxim users. Data was collected using a questionnaire, and the analysis method employed is quantitative, using statistical tests with SPSS. This study utilizes multiple linear regression analysis, validity tests, reliability tests, coefficient of determination, t-tests, and F-tests. The results of this study indicate that promotion has a positive and significant effect on purchasing decisions for online transportation in Bengkulu City using Maxim, where t-value 3.660 > t-table 1.984 with a significance level of 0.000 < 0.05. Additionally, consumer trust has a positive and significant effect on purchasing decisions for online transportation in Bengkulu City using Maxim, where t-value 2.486 > t-table 1.984 with a significance level of 0.015 < 0.05. Furthermore, service quality also has a positive and significant effect on purchasing decisions for online transportation in Bengkulu City using Maxim, where t-value 2.064 > t-table 1.984 with a significance level of 0.042 < 0.05. Simultaneously, promotion, consumer trust, and service quality have a positive and significant effect on purchasing decisions for online transportation in Bengkulu City using Maxim, where F-value 26.678 > F-table 2.700 with a significance level of 0.000 < 0.05.